(untitled) (Journal of Science and Technology, 2016)
Pollen grains from fresh anthers of three species and a variety of Ocimum occurring in South- western Nigeria were collected and acetolysed. This was in an attempt to use the pollen charac- teristics to delimit, classify and trace probable evolutionary relationships among the taxa. The structural morphology of the pollen grains carried out with a light microscope is reported. Char- acters measured on the pollen grains were pollen diameter, pollen wall thickness, depth of colpi, distance between colpi and pore diameter. This was done with the aid of an ocular micrometer. Number of pores per pollen was counted. Pollen grain sizes of the species and the variety of Ocimum studied fall into two groups, Media (diameter 25-50µm) and Magna (diameter 50- 100µm). All the species and the variety had acolpate and hexacolpate pollen grains. Heptacol- pate and octacolpate pollen grains which are advanced types of pollen grains were encountered in O. canum only. These advanced types of pollen grains are a mark of recent evolutionary de- velopment in the species.